MENGELOLA PROSES TIM - Raharso, Sri (Program Studi Pendidikan Manajemen Perkantoran, 2012)
Work teams has become relatively common in organizations because brilliant execution that can onlybe done with teamwork. A team as a group of individuals who work together under a unity of purpose,as a united front. But develop team is not easy, take some years. When team leaders focus primarily onhard business tools, such as schedule, budget, and scope, they can lose sight of a more subjective aspectof the project—the team member. Each person brings a unique set of experiences and knowledge to theteam. Equally important are the social and behavioral skills that each individual uses to interact withother team members in forming a cohesive and productive team. At a team’s inception, individuals do notinstantly become a cohesive and unified group. Each person has a personal norm that dictates his or herself-perceptions and exhibited behaviors in social settings. In a group, an individual uses these learnedbehaviors to influence others and, in turn, is influenced by other individuals on the team. Hence, processthat happened in team must managed in careful. In this case, this paper discusses level of team growth,cohesion, and norm in team.